The Frames of Romance Scamming - Faber, Pamela (Research in Language, 2024)
This paper studies love fraud or romance scamming as scripted communication within a commercial transaction frame. The main participants are the seller (fraudster), buyer (victim), goods (long-term romantic relationship), and money (paid by the victim). The data for this study were collected from 53 conversations between fraudsters and the author. The romance scamming frame was activated by language and lexical choices and geared to winning her trust. The process took place in stages or subframes that guided the victim towards the payment of a large sum of money. These subframes also corresponded to the different ‘subformats’ of an authentic script or ‘format’ used by romance scammers in West Africa.